Artificial Ionospheric GPS Phase Scintillation Excited During High‐Power Radiowave Modulation of the Ionosphere. Issue 6 (15th June 2018) - Mahmoudian, A.; Scales, W. A.; Taylor, S.; Morton, Y.; Bernhardt, P. A.; Briczinski, S. J.; Ghader, S.
Abstract: Artificial ionospheric GPS phase scintillation effects excited during the fourth gyroharmonic (4 f c e ) heating at the High Frequency Active Auroral Research Program along with a theoretical model for the associated ionospheric irregularities are presented in this paper. The generation mechanism and time evolution of artificial GPS phase scintillation have been investigated using the simultaneous collected data including GPS scintillation, wideband stimulated electromagnetic emissions (WSEE), and ionosonde. The generation of the broad upshifted maximum, a WSEE spectral line associated with super small striation, through the four‐wave decay instability is studied using a theoretical model. The possible role of decameter‐scale irregularities within the Fresnel zone as well as super small striation in the GPS phase scintillation is investigated using the correlation of WSEE features with the scintillation data. Time evolution of slant total electron content (STEC) data and modulation of GPS phase and amplitude are compared with the theoretical model to study the plasma waves involved in the scintillation process. The similarity of theoretical and previously developed computational results, with the observations, is discussed. Specifically, the time evolution of STEC fluctuations including an initial growth period and subsequent saturation has been compared with the estimated growth rate of upper hybrid and electron Bernstein waves using the theoretical calculations as well as previous computational results. The damping process associated with the decay of STEC fluctuations after the initial growth has been investigated by considering the nonlinear behavior of electron Bernstein waves obtained from the computational model. Key Points: The nonlinear behavior of electron Bernstein waves obtained from the computational model is used to investigate the damping process associated with the decay of STEC fluctuations Correlation of WSEE and GPS phase scintillation data with computational and theoretical calculations is presented Future experiments in determining the exact characteristics of four‐wave PDI and GPS scintillation based on the theoretical calculations are being planned